ANALISIS BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN TOTAL PENJUALAN DAN LABA (STUDI PADA UMKM RIZKY BAROKAH MALANG) - Naro, Ikhsan Aprilian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Break-even point analysis is an analytical technique used by management to determine at what level company neither suffer a loss nor gain profit. Break-even point analysis is used by companies to determine the sales that must be achieved so that they do not suffer any loss. The purpose of this research is to describe the application of break-even point analysis and to describe the sales planning and the minimum sales that must be achieved by Rizky Barokah, an MSME, in order to reach the desired profit in the period of 2017. The descriptive research uses the company’s sales data from 2014 to 2016, where the data of 2016 is used as the basis for 2017’s sales volume and and profit planning. The results of the analysis show that the company’s BEP mix is IDR 363,408,491.71, or at the level of 28,739 units. The calculation of margin of safety is 56.72%. The company wants to increase the profit up to 31.13%. Therefore, the total sales should reach 65,925 units, where the sales of original fermented soybean chips should reach 24,882 units, flavored fermented soybean chips should reach 23,744 units, apple chips should reach 8,710 units, and jackfruit chips should reach 8,619 units.Keywords : break-even point, sales planning, profit